Concepção de método simplificado de levantamento e análise de defeitos em vias não-pavimentadas - Silva, Francisco Rafael Ribeiro da (2007)
The implantation of the management systems has always been a challenge for the functioning parts which are responsible for the roads of a region. Such challenge becomes even bigger when the implantation of this kind of management has to be applied to roads which are not paved. It is important to consider, in this case, the bigger extension when compared with roads with some kind of overlay. We may also consider the scarcity of studies and works published in this area which complicates even more its practical application. The present work aims to contribute for the arrangement of the pavement management system (PMS), focusing its first stage, the field survey, besides the posterior analysis of the data obtained. We have as a basis the research accomplished in the USA as the ones by Eaton et al. (1987), we also tried to adapt and innovate new techniques of field survey, aiming to facilitate the achievement of data which must be inserted in methods of evaluation of the bearing conditions of the unpaved roads. The roads AQZ-01, AQZ-02 and AQZ-03, located in the district of Aquiraz, were chosen for the accomplishment of this research, once they had already been used in previous works which followed the same line of research, the management of unpaved roads. As a conclusion for this work, we hope to close this research cycle which was started in 2003 with the studies of Correia (2003), Moreira (2003) and Nunes (2003) and were recaptured in 2006 by Almeida (2006) and Santana (2006); each of them working at a specific stage of a PMS directed to the unpaved roads and that is applicable to the reality of the roads in Ceará and which can also be used by the municipal organs, helping in the management of the roads in general as well as of the unpaved ones.